(untitled) (London Journal of Research In Management & Business, 2025)
Gross Domestic Product (GDP) of a nation is an important index which reflects health and performance of an economy and its aggregate income. In this paper, annual GDP data of three Asian economies for the time period 1960 2022 is used for predictive Autoregressive Integrated Moving Average (ARIMA) modelling. ARIMA is a time series analysis method that can capture temporal tendencies and trends in the data series. We seek to gain insights into the future expected trajectory of economic growth in the selected countries through long-term predictions for the time period 2023 2037. Augmented Dick Fuller (ADF) test is used to asses stationarity of the data. In the present empirical study, stationarity at the second order differencing with ARIMA (0, 2, 2) model is identified to predict GDP of China, ARIMA (2, 2, 1) model is identified to predict GDP of Pakistan, and ARIMA (0, 2, 1) model is identified to predict GDP of Bangladesh for the next 15 years. The finding shows that the forecast values of Chinas GDP will be 14123.90 per capita in 2023 and 29842.64 per capita in 2037 Pakistans GDP will be 1589.066 per capita in 2023 and 2115.446 per capita in 2037, and Bangladeshs GDP will be 2880.167 per capita in 2023 and 5566.303 per capita in 2037, Our study provides skeletal guidance for governmental bodies and direct investors who rely for business planning and strategizing of the resources on reliable predictions of GDP per capita. Advance knowledge about futuristic GDP level enables administrators, investors and policymakers to make informed economic decisions that may steer economic growth, stability and development in an optimum direction.